Akibat Hukum Peraturan Daerah Sumatera Barat Tentang Penyelenggaraan Wisata Halal Dalam Meningkatkan Investasi Lokal - Ulfanora Nanda; Dian Amelia; Nanda Utama; Arya Putra Rizal Pratama (Universitas Airlangga, 2023)
AbstractStructuring the tourism sector is a concern for the Regional Government, especially in West Sumatra, which continues to develop halal tourism as a hall mark of adaik basandi syara’ syarak basandi Kitabullah. The role of the Government of West Sumatra has been seen in structuring Halal Tourism after the issuance of West Sumatera Provincial Regulation concerning Organizing Halal Tourism. Halal tourism is a set of additional services for amenities, attractions and accessibility that are intended and provided to meet the experiences, needs and desires of Muslim tourists and other tourists who need them.West Sumatra part of the preservation of halal products as well as the application of the upholding philosophy of Islamic and customary values as the foundation of the life of the Minangkabau. In implementing halal tourism, the Government of West Sumatra is responsible for developing Halal Tourism business including providing investment incentives, facilitating investment facilities, as well as facilitating infrastructure facilities in implementing Halal Tourism. The results of this study explain that Regional Regulation concerning the Implementation of Halal Tourism in general has been implemented by the government, with so far establishing halal tourism destinations, including the Baso Pagaruyung Palace in Tanah Datar, Twin Lakes in Solok Regency, and the Islamic Center in Padang. The concept of halal tourism is not to prescribe a place, but rather to provide additional services to tourists who prioritize Muslim tourists and other tourists who need it.Keywords: Halal Tourism; Additional Service; Local Economy. AbstrakPenataan sektor wisata menjadi suatu concern Pemerintah Daerah terutama di Sumatera Barat yang terus mengembangkan Wisata halal sebagai ciri khas dari adaik basandi syara’ syarak basandi kitabullah. Peran Pemerintah Sumatera Barat telah terlihat dalam penataan Wisata halal setelah terbitnya Peraturan Daerah Provinsi Sumatera Barat tentang Penyelenggaraan Wisata Halal. Wisata halal sebagai perangkat layanan tambahan amenitas, atraksi, dan aksesibilitas yang ditujukan dan diberikan untuk memenuhi pengalaman, kebutuhan, dan keinginan wisatawan muslim dan wisatawan yang lain yang membutuhkannya. Keberadaan Wisata halal di Sumatera Barat bagian dari pelestarian produk halal sebagaimana penerapan dari junjungan tinggi filosofi Nilai-nilai Islam dan Adat sebagaimana dasar dari pijakan hidup masyarakat MinangKabau. Dalam penyelenggaraan wisata halal, Pemerintah Sumatera Barat bertanggungjawab dalam pengembangan usaha Pariwisata Halal meliputi pemberian insentif investasi, fasilitas kemudahan investasi, serta fasilitas kemudahan infrastruktur dalam pelaksanaan Pariwisata Halal. Hasil penelitian ini menjelaskan bahwa Penyelenggaraan Pariwisata Halal secara umum telah dilaksanakan oleh pemerintah, dengan sejauh ini telah menetapkan destinasi pariwisata halal antara lain yaitu Istana Baso Pagaruyung di Tanah Datar, Danau Kembar Kabupaten Solok, dan Islamic Center di Padang Panjang. Konsep wisata halal ini bukanlah mensyariat suatu tempat, melainkan lebih kepada pelayanan tambahan (addcended service) yang diberikan kepada wisatawan yang di utamakan wisatawan muslim dan wisatawan lain yang membutuhkan.Kata Kunci: Wisata Halal; Pelayanan Tambahan; Ekonomi Lokal.